Pemulihan sosial berbasis pelayanan sosial Muhammadiyah pasca bencana gempa bumi Cianjur 2022 - Ramadhan, Erik Habib Fajri; Sukmana, Oman; Habib, Achmad (LP2M Universitas Sarjanawiyata Tamansiswa, 2023)
Disaster social services are very important in helping disaster-affected people to overcome the difficult situations they face and restore their lives. The purpose of this research is to study the effectiveness and efficiency of social services in helping people affected by disasters. This research is a literature review with the main source being the results of the 2023 Muhammadiyah Disaster Management Center report. The data analysis technique in this research is through reduction, presentation, and conclusion drawing. The results showed that in the emergency response to the November 2022 Cianjur earthquake, Muhammadiyah provided services 1.) Effective and transparent logistics services 2.) Health services that involve coordination with various policy makers. 3.) Shelter sector services that involve the construction of emergency shelters with family principles. 4.) WASH sector services that meet the sanitation and clean water needs of affected communities through the construction of boreholes, construction of emergency toilets, distribution of water reservoirs, pipelines, waste management, and PHBS socialization. 5.) Psychosocial services that focus on restoring the mental and psychological conditions of residents, especially children. 6.) Emergency education services that involve coordination with the education office, training for teachers, developing emergency education modules, school assistance, and establishing emergency schools. 7.) Services in the field of Search and Rescue (SAR).